Accurate design of porous g-C3N4+x with greatly extended visible-light response for enhanced photocatalytic performance and mechanism insight for environmental remediation. (1st December 2022) - Liu, Qianqian; Du, Xing; Gu, Huajun; Cheng, Miao; Hu, Jing; Wei, Tao; Li, Wanfei; Liu, Bo; Dai, Wei-Lin
Abstract: Nitrogen-rich graphite carbon nitride has attracted considerable attention due to its low band gap and widespread potential application. Herein, a series of porous g-C3 N4+ x materials are developed by pyrolysis of 3-amino-1, 2, 4-triazole (C2 H4 N4 ) and mesoporous silica template (KIT-6). The pore diameters can be precisely tuned by controlling the proportion of C2 H4 N4 and KIT-6. A variety of characterizations were conducted to analyze the correlation between structure and photocatalytic performance toward the degradation of rhodamine B. It was found that, the synthesized porous g-C3 N4+ x exhibited a narrower band gap of 1.43 eV, which significantly extended its visible-light responsive range. Moreover, the enhanced N content and adjustable porous diameter effectively increased the separation efficiency of photogenerated electron–hole pairs. Therefore, remarkably improved photocatalytic activity was achieved, which was 5.2 times higher than that of bulk g-C3 N4+ x, and presented super stability as well. Additionally, the possible photocatalytic mechanism was proposed and verified. These findings shed light on a new facile way to fabricate high-performance photocatalytic materials and provided new opportunities for environmental remediation.